Anti-ulcer activity of Cestrum nocturnum leaf in ethanol- and indomethacin-induced ulcer models - Saleem, Uzma; Haq, Ejaz ul; Ahmad, Bashir; Saleem, Mohammad (Bangladesh Journal of Pharmacology, 2017)
This study was planned to explore the antiulcer activity of the methanolic and n-hexane extracts of Cestrum nocturnum leaf against ethanol- and indomethacin-induced ulcer models in rats. The rats were administered orally vehicle in normal control group, methanolic and n-hexane extracts at doses 300, 500, 700 mg/kg, in treated groups and omeprazole 20 mg/kg, as standard drug. The gastric tissues/contents were examined to determine the ulcer index, antiulcer activity, gastric pH, gastric juice volume and acidity. Both extracts showed dose-dependent increase in antiulcer activity (%) in both ulcer models. Histopathology also supported these results. Gastric pH significantly increased while the gastric juice and acidity significantly decreased in the treatment groups of both ulcer models indicating the anti-secretory effect of extracts. It may be concluded that C. nocturnum protect gastric mucosa by decreasing gastric juice, acidity and increasing the gastric pH. Video Clip of Methodology: 6 min 58 sec: Full Screen Alternate